Network Broadcasting System (NBS): Implementation and Its Obstacles - Amin Shabana (Universitas Muhammadiyah Jakarta, 2019)
The draft revision of Law No.32/2002 on broadcasting currently has entered the stage of legislation body of DPR RI (Baleg). The revision eliminated the obligation of the Network Broadcasting System (NBS) for Private Broadcasting Institutions (LPS) considered have neglected the public interest of the broadcasting sector. For many groups, especially civil society, this new policy regarding SSJ is a step backward. The decentralization spirit of the broadcasting industry is threatened to be continued. While the implementation of the NBS itself has been carried out half-heartedly. The purpose of this study is to know the implementation of NBS carried out by the LPS designated as the central stations and the obstacles faced in managing the implementation of NBS with network stations located in the region. The theory used in this study are broadcasting, mass media and NBS. This study uses a qualitative approach with descriptive method. Data collection techniques: interview with the Central Indonesian Broadcasting Commission, study literature, and documentation; The validity test of the data is through informant triangulation to organization that conduct broadcast advocacy, Remotivi. The results of this study indicate that NBS implementation is still not running optimally. LPS still has a reluctance in preparing infrastructure facilities to implement NBS. Meanwhile the impact of NBS at the local level is also increasingly complex in various sectors of life. Various obstacles start from regulation, political will of all NBS stakeholders and weak supervision caused NBS still far from expectations. This situation makes the centralistic broadcasting system remain dominant. Keyword: Decentralization, Broadcasting Industry, Network Broadcasting Systems